Good Corporate Governance (GCG) sebagai strategi peningkatan kinerja bank syariah di Indonesia - Arini, Titania Putri (Maliki Interdisciplinary Journal, 2025)
Islamic banking plays a strategic role in promoting national economic growth based on Islamic principles of justice, transparency, and public welfare. Amidst the dynamics of global financial competition, Islamic banks are required to implement effective strategic management to compete with conventional financial institutions. This article aims to examine the concept of strategic management in Islamic banking and analyze its application in Bank Syariah Indonesia (BSI) as a case study. This study analyzes the implementation of Good Corporate Governance (GCG) as a strategic approach to enhance the performance of Islamic banks in Indonesia. The research applies a library-based method, reviewing academic literature, financial reports, and regulations from the Financial Services Authority (OJK, 2020). The discussion focuses on three key aspects: (1) the principles of amanah (trustworthiness) and transparency as ethical foundations of Sharia governance (Nisrina, 2018; Karim, 2019); (2) the role of the Sharia Supervisory Board (DPS) and risk management in ensuring compliance (Natalina & Zunaidi, 2021); and (3) the impact of GCG on public trust and financial performance (Nurhayati & Azizah, 2023; Rahmadhi & Rialdy, 2024). The results show that GCG based on amanah and transparency enhances customer trust, institutional reputation, and operational efficiency (Rohmandika, 2024). DPS plays a vital role in maintaining Sharia compliance and financial stability. The study recommends strengthening DPS capacity, improving transparency, and integrating amanah and maslahah values into governance practices (Karim, 2019).